Laboratory study for optimal mixing scheme of pervious concrete containing additive of microsilica fume based on maximum compressive strength and permeability - Mehdi Komasi (Iranian Society of Structrual Engineering (ISSE), 2021)
One of the useful and efficient ideas in pavement and flooring is use of permeable concrete which is called pervious concrete. Pervious concrete that has many economic and especially environmental impacts can be used for reducing surface runoff during rainfall, delaying the entry of rainwater into the sewage system due to its absorption by the ground, improving the quality of groundwater due to lack of water flow from the ground and contact with possible contamination. In this study, four different mix design were used for three types of aggregating aggregates, which contains 12 general mixing states, including samples of simple concrete and examples of microsilica fume additives. At the end, compressive strength and permeability tests have been carried out on them. The results obtained from the research show that the individual with a higher density or, in other words, a finer grain size, exhibited a compressive strength of 9 Mpa, but had a 15% lower permeability. In general, according to the results of these experiments, the factors affecting the density of pervious concrete can be expressed by the size of the aggregates, the efficiency and the amount of microsilica fume. Because of its superplasticizering, the microsilica fume increases the strength and durability of concrete but reduces porosity of concrete, but its permeability is still acceptable to simple concrete. Finally, the optimum aggregate for compressive strength and optimal permeability, is obtained in third type of aggregating in this study, In which half of the aggregates have been formed of residues on the sieve of 3.8 and the remaining half of the residues on the sieve of 4 and depending on the need for greater resistance or permeability, parameters such as water to cement ratio, sand/cement ratio and microsilica fume addition can be obtained, which has been investigated in this study.